The social understanding of mental health crisis in dementia - Bosco, Alessandro (2020)
Introduction: Dementia is a neurodegenerative and psychosocial condition, affecting cognition and leading to experiences of crisis that can prove destabilising for the person with dementia and their family carers. In the UK, the Prime Minister’s Challenge on Dementia 2020 calls for post diagnosis secondary support for crisis care as key to reduce hospital admissions, care burden and maintain the person with dementia in a familiar environment. Although at community level, crises are managed through multidisciplinary teams, the provision of these teams is not consistent across the care sector, as different teams may have different structure and provide different therapeutic options for resolution of crisis. Research on the experience of crisis care is still limited. For this reason, the study aims to explore (i) the experience of managing crises in dyads, people with dementia and their carers, and (ii) the way the person with dementia is actively involved by teams managing crisis in dementia when delivering professional support. Owing to the variety of experiences and triggers that crises may entail, crises were operationalised in more general terms and according to mechanisms underlying the behavioural process. A Crisis was defined as ‘a process in which a stressor(s) causes an imbalance that requires immediate decision to reach a crisis resolution. In the presence of an unresolved crisis, the cycle continues.